Evaluasi Kesiapan Puskesmas Dalam Penerapan Sistem Informasi Manajemen Puskesmas (Simpus) Berbasis Web di Puskesmas Pajang Surakarta - Wulan, Diajeng Citro; , Sri Darnoto S.KM M.PH; , Arief Kurniawan NP, SKM, M.PH (2015)
The presence of application city health departement Surakarta that at begining of 2015, the publichealth center management system in the first public health center will developed into that based on the dekstop and the user is not flexible and based on website. The aim of research is to analyze readiness Pajang health center in the implementation public health center management information system. The research use descriptive in the planning and police based on the UU no 11 tahun 2008 about ITE and the user of meeting in the Surakartacity health department. The supporting facility include the socialization web health center management information system. The human resource are still less, with the colletion, the process, persent data, giving health information visiting work, evaluating implementation public health center. The organization supporting is the authority that will be given to section of health information system to manage the implementation health center management information system under the field of health promotion